INFLUENCE OF MIDDLE ENGLISH NORTHERN DIALECTS ON THE DEVELOPMENT OF THE ENGLISH LANGUAGE - Hyryn, O. (Studia Philologica, 2020)
The article deals with the phonetic, grammatic and lexical features which penetrated into the London Dialect from the Middle English Northern and North-Eastern dialects and evenyually were fixed in the literary language. The article claims that the penetration of the Northern features took place as the result of the London dialect base shift which took place due to the extralinguistic reasons, namely by social and demographic reasons. The article describes both direct influence (lexical) and indirect (partially phonetic and partially grammatic). The article claims that systemic changes in English, such as reduction of unstressed syllables and concequent simplification of grammatical paradigms were greatly fascilitated by the influence of Northern dialects on the London dialect in Late Middle English period Key words: Middle English Period, Scandinavian incursions, London dialect, Dialectal base, reduction of unstressed syllables, word-building paradigm, semantic shift.